Marketing Mix Factors Influencing Customers’ Services Selection for Avani Luang Prabang Hotel - Vannathy, Mr Phettakoun; Sifongxay , Sangthong; Somsamone, Vilayphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to examine the level of marketing mix factors that influence customers’ selection of services at Avani+ Luang Prabang Hotel. To assess the level of customer service selection at Avani Luang Prabang Hotel. To analyze the marketing mix factors that significantly affect customers’ selection of services at Avani Luang Prabang Hotel. The target population comprises customers who have used the services of Avani+ Luang Prabang Hotel. A non-probability sampling method was employed, specifically using convenience sampling, with a total of 384 respondents. Data were analyzed using SPSS software, applying both descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (multiple regression analysis). The study found that, overall, the level of marketing mix factors influencing customer selection is at the highest level. These factors include location, personnel, process, physical evidence, price, product, and promotion. The analysis of customer service selection at the hotel revealed a high level of overall satisfaction. Key influencing aspects include the hotel’s strong reputation and positive image, competitive pricing and sales promotions, robust security system, high service quality, adherence to service standards, strategic location, and variety of available services. Furthermore, the regression analysis indicated that price, personnel, process, and physical evidence significantly affect customers’ selection of services at Avani+ Luang Prabang Hotel, with statistical significance at the 0.05 level.